High-current breakdown of the quantum Hall effect and electron heating in InSb/AlInSb - Alexander-Webber, J; Baker, A; Buckle, P; Ashley, T; Nicholas, R (2012)
We report measurements of the temperature and electric field dependent breakdown of the quantum Hall effect in two-dimensional InSb/AlInSb heterostructures. The electron temperature T e is studied as a function of electric field and it is shown that the energy loss rates of electrons to the lattice follow a (Te3-TL3) dependence for 2K